High frequency of antimicrobial drug resistance of diarrheagenic Escherichia coli in infants in Peru. - Ochoa, Theresa J. (2014)
Abstract. In a prospective passive diarrhea surveillance cohort study of 1,034 infants of low socioeconomic communities in Lima, Peru, we determined the prevalence and antimicrobial drug susceptibility of the diarrheagenic Escherichia coli . The prevalence of diarrheagenic E. coli was 29% (161 of 557) in children with gastroenteritis and 30% (58 of 195) in the control group without diarrhea. The most common E. coli pathogens in diarrhea were enteroaggregative E. coli (EAEC) (14%), enteropathogenic E. coli (EPEC) (7%), diffusely adherent E. coli (DAEC) (4%), and enterotoxigenic E. coli (ETEC) (4%). Diarrheagenic E. coli as a group exhibited high levels of antimicrobial drug resistance in diarrheal cases to ampicillin (85%), cotrimoxazole (79%), tetracycline (65%), and nalidixic acid (28%). Among individual E. coli groups in patients with diarrhea, DAEC and EAEC exhibited significant higher frequencies of resistance to ampicillin, cotrimoxazole, tetracycline and nalidixic acid than EPEC and ETEC. Antimicrobial drug resistance to ampicillin and cotrimoxazole were more frequent in E. coli isolated from diarrheal samples than controls, which reflected greater antibiotic exposure in patients with gastroenteritis.